Factors Influencing Online Academic Performance Among University Students - Ng, Hee Song; Kuek, Thiam Yong; Chen, Kah Huan; Chang, Jia Hao; Chee, Yu Ping; Chen, Li Jun; Pramana, I Made Gede Andita; Indrayana, Andy Ramadhan; Singh, Ayushi; Zirape, Saurabh (AIBPM Publisher, 2023)
In recent years, the COVID-19 pandemic has made a significant impact on education around the world. Nevertheless, the governments of these nations have discovered a way to try to alleviate the education crisis during the pandemic by offering online academic classes. Students can continue to study without interfering with their future courses, and they will not underestimate their studies since they have been isolated at home for a long time. The purpose of this research is to investigate the factors influencing online academic performance among university students. This study used survey questionnaires, and a total of 155 university students were picked to take part in this research via Google Forms. The results indicate that academic staff responsibilities, ease of use and university guidance are significantly related to online academic performance. However, course design and content, motivation, perceived usefulness and student willingness are not significantly related to online academic performance.